Regional experience of implementing the state control risk-based model in vocational education: sociological survey analysis - S. E. Titor (Вестник университета)
The control and supervisory state function reform by a new risk-oriented model implementing has two major complementary goals: reducing the administrative burden on business while enhancing the safety of legally protected values. For the education sector, this model has been implementing since 2015, actualising the study of its applying experience by vocational organisations in the Russian regions under state supervision. The purposes of the study are to investigate the readiness of controlled entities to effectively applying of risk-based state control model, and to collect data for the development of new proposals to improve framework and law enforcement practice of control and supervision activities in education. The study is based on expert assessment of a new model application experience and an analysis of controlled entities opinions on used methodologies. For the first time, the relation of professional educational organisations to indicated problems was investigated and the respondents’ proposals for improving new processes were analysed in the article. The scientific novelty of the study is the applying of